TRANSPORTATION ISSUES IN THE DELIVERY OF GTL PRODUCTS FROM ALASKAN NORTH SLOPE TO MARKET - Chukwu, Godwin (University of Alaska Fairbanks (United States), 2004)
The Alaskan North Slope (ANS) is one of the largest hydrocarbon reserves in the United States where Gas-to-Liquids (GTL) technology can be successfully implemented. The proven and recoverable reserves of conventional natural gas in the developed and undeveloped fields in the Alaskan North Slope (ANS) are estimated to be 38 trillion standard cubic feet (TCF) and estimates of additional undiscovered gas reserves in the Arctic field range from 64 TCF to 142 TCF. Because the domestic gas market in the continental United States is located thousands of miles from the ANS, transportation of the natural gas from the remote ANS to the market is the key issue in effective utilization of this valuable and abundant resource. The focus of this project is to study the operational challenges involved in transporting the gas in converted liquid (GTL) form through the existing Trans Alaska Pipeline System (TAPS). A three-year, comprehensive research program was undertaken by the Petroleum Development Laboratory, University of Alaska Fairbanks, under cooperative agreement No. DE-FC26-98FT40016 to study the feasibility of transporting GTL products through TAPS. Cold restart of TAPS following an extended winter shutdown and solids deposition in the pipeline were identified as the main transportation issues in moving GTL products through the pipeline. The scope of work in the current project (Cooperative Agreement No. DE-FC26-01NT41248) included preparation of fluid samples for the experiments to be conducted to augment the comprehensive research program.